2017
DOI: 10.1111/padm.12330
|View full text |Cite
|
Sign up to set email alerts
|

Context matters: A Bayesian analysis of how organizational environments shape the strategic management of sustainable development

Abstract: Public administration scholars have argued the need for a ‘general theory’ linking strategic management to the context in which public organizations operate. Understanding the interplay between organizational contexts and strategic management responses to urban sprawl and greenhouse gas (GHG) emissions remains an underexplored avenue for empirical advancement of this goal. Using 2015 survey data, we employ a novel Bayesian item response theory (IRT) approach to test how land use policy comprehensiveness, organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 57 publications
1
17
0
1
Order By: Relevance
“…For example, local governments make varying policy commitments to curtail sprawling growth, preserve a quality of life and opportunities for future citizens, address social inequality, or remediate environmental damage (Deslatte & Swann, 2016; Fiorino, 2018; Portney, 2013). The processes for implementing and monitoring these policy commitments may or may not materialize through strategic planning processes (Deslatte & Swann, 2017), which sometimes identify performance indicators and depend on existing or new performance management systems (Krause, Hawkins, Park, & Feiock, 2019). However, only the largest and highest-capacity cities tend to engage in sustainability performance management (Niemann & Hoppe, 2018).…”
Section: The Role Of Eo In the Capacity–strategy–performance Linkagementioning
confidence: 99%
See 3 more Smart Citations
“…For example, local governments make varying policy commitments to curtail sprawling growth, preserve a quality of life and opportunities for future citizens, address social inequality, or remediate environmental damage (Deslatte & Swann, 2016; Fiorino, 2018; Portney, 2013). The processes for implementing and monitoring these policy commitments may or may not materialize through strategic planning processes (Deslatte & Swann, 2017), which sometimes identify performance indicators and depend on existing or new performance management systems (Krause, Hawkins, Park, & Feiock, 2019). However, only the largest and highest-capacity cities tend to engage in sustainability performance management (Niemann & Hoppe, 2018).…”
Section: The Role Of Eo In the Capacity–strategy–performance Linkagementioning
confidence: 99%
“…In the realm of sustainability, hostility toward policy goals can have a dampening effect on policy innovations, such as when Tea Party groups during the 2010 U.S. congressional elections began targeting cities which had committed to climate protection (Krause, Yi, & Feiock, 2016). Wang and colleagues (2012) found citizen and stakeholder engagement strategies were positively related to organizational capacities, whereas Deslatte and Swann (2017) found political capacity positively influenced strategic planning for smart growth. But they also found that a perceived lack of stakeholder support within the business community may fuel management efforts to secure fiscal resources through grants or issuing debt (Deslatte & Swann, 2017).…”
Section: The Role Of Eo In the Capacity–strategy–performance Linkagementioning
confidence: 99%
See 2 more Smart Citations
“…We also consider the role of the organization’s performance context in shaping how frontline employees are likely to interpret and respond to the unattainable performance goals. Contingency theory is a core component of modern management scholarship (Donaldson, 1987; Hofer, 1975; Prescott, 1986) and is increasingly being integrated into public management scholarship as researchers strive to consider the contextual factors that can condition the effect of management on organizational outcomes (e.g., Boyne, James, John, & Petrovsky, 2011; Deslatte & Swann, 2017; Ryu & Lee, 2013; Stazyk & Goerdel, 2011; Zambrano-Gutiérrez, Rutherford, & Nicholson-Crotty, 2017). Drawing from the work of Sitkin et al (2011), we suggest that organizational performance will moderate how unattainable goals affect collective turnover among a public service organization’s frontline employees.…”
Section: Introductionmentioning
confidence: 99%